Study Design and Rationale of EXPLORER-HCM: Evaluation of Mavacamten in Adults With Symptomatic Obstructive Hypertrophic Cardiomyopathy. (June 2020) - Ho, Carolyn Y.; Olivotto, Iacopo; Jacoby, Daniel; Lester, Steven J.; Roe, Matthew; Wang, Andrew; Waldman, Cynthia Burstein; Zhang, David; Sehnert, Amy J.; Heitner, Stephen B.
Abstract : Background: Obstructive hypertrophic cardiomyopathy (oHCM) is characterized by unexplained left ventricular (LV) hypertrophy associated with dynamic LV outflow tract obstruction. Current medical therapies are nonspecific and have limited efficacy in relieving symptoms. Mavacamten is a first-in-class targeted inhibitor of cardiac myosin, which has been shown to reduce LV outflow tract obstruction, improve exercise capacity, and relieve symptoms of oHCM in the PIONEER-HCM phase 2 study. Methods: EXPLORER-HCM is a multicenter, phase 3, randomized, double-blind, placebo-controlled trial to investigate the efficacy and safety of mavacamten in treating symptomatic oHCM. Eligible adults with oHCM and New York Heart Association Functional Class II or III are randomized 1:1 to receive once-daily, oral mavacamten, or matching placebo for 30 weeks. The primary composite functional end point is clinical response at week 30 compared to baseline defined as either (1) an increase in peak oxygen consumption ≥1.5 mL/kg/min and reduction of at least one New York Heart Association class; or (2) an improvement of ≥3.0 mL/kg/min in peak oxygen consumption with no worsening of New York Heart Association class. Secondary end points include change in postexercise LV outflow tract gradient, New York Heart Association class, peak oxygen consumption, and patient-reported outcomes assessed by the Kansas City Cardiomyopathy Questionnaire and a novel HCM-specific instrument. Exploratory end points aim to characterize the effect of mavacamten on multiple aspects of oHCM pathophysiology. Conclusions: EXPLORER-HCM is a phase 3 trial in oHCM testing a first-in-class, targeted strategy of myosin inhibition to improve symptom burden and exercise capacity through reducing LV outflow tract obstruction. Results of this trial will provide evidence to support the first disease-specific treatment for HCM. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03470545. Abstract : Supplemental Digital Content is available in the text.